메타버스 플랫폼의 사용자 리뷰 데이터 분석 연구 - 아바타 기반의 소셜형 메타버스 플랫폼을 중심으로 - 임정민(Jeong-Min Lim); 전우정(Woo-Jeong Chon) (디지털콘텐츠학회논문지, 2023)
애플 등 글로벌 빅테크 기업에서 MR(혼합현실)기기를 공개하면서 메타버스에 대한 수요와 관심이 증대되고 있는 시점에, 메타버스 사용자의 만족도를 높이기 위해 사용자 분석의 중요성이 강조되고 있다. 메타버스 플랫폼 사용자의 경험이 담긴 리뷰데이터 분석을 통해 사용자의 경험을 긍정적으로 이끄는 사용요인을 확인할 필요가 있다. 이를 위해 아바타 꾸미기 콘텐츠 중점의 소셜형 메타버스 플랫폼 세 가지를 선정한 후 텍스트마이닝을 통해 감성단어 사전을 제작하였고, 이를 바탕으로 메타버스 사용 경험에 몰입 또는 방해요소로 작용하는 요인에 대한 맥락 고찰을 진행하였다. 그 결과, 꾸미기 콘텐츠의 다양한 선택지 제공과 간단한 오락 요소가 포함된 소셜 콘텐츠에 대한 공통적인 니즈가 있음을 발견하였고, 앱 설치와 인증 과정에서의 잦은 오류, 개인 정보 유출은 부정적인 요소로 확인되었다. 본 연구를 통해 사용자의 지속사용의도를 높이는 서비스 개선 방향 설정, 소셜형 메타버스 플랫폼 제작 시 운영 및 마케팅 전략 수립에 도움을 줄 수 있을 것으로 기대한다. With the global unveiling of MR(Mixed Reality) devices by major technology companies, there is a growing demand and interest in the metaverse. This underscores the significance of conducting metaverse user analysis within this evolving digital realm. To better understand the factors that contribute positively to user experience in the metaverse, this study employs review data analysis. For this purpose, three social metaverse platforms that emphasize avatar decoration content were selected. Then, text mining was conducted to create an emotional word dictionary and the relationship between words was analyzed to gain contextual insights into metaverse usage factors. As a result, it was found that there was a common need for social content that included various options for decorative content and simple entertainment elements, and frequent errors in the application installation and authentication process and personal information leakage were identified as negative factors. This study is expected to help set the direction of service improvement that increases users' intention to continue using, and to establish operational and marketing strategies when creating a social metaverse platform. KCI Citation Count: 1